1996
DOI: 10.1046/j.1524-475x.1996.40207.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of oxygen on human dermal fibroblasts: acute versus chronic hypoxia

Abstract: The observation that many chronic wounds are ischemic has spurred a series of studies evaluating the response of cells exposed to hypoxia. To date, these studies have shown largely beneficial effects from hypoxia, such as increased cellular replication and procollagen synthesis. These findings are counter-intuitive from a clinical standpoint because cellular growth and synthetic function are known to be retarded in chronic ischemic wounds. We have established an in vitro system in which human dermal fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 1 publication
6
67
0
1
Order By: Relevance
“…After 72 hours exposure to 1% oxygen, the proliferative rate of fibroblasts increases by 71% [10]. Low oxygen tensions have been shown to initiate clonal expansion of fibroblasts [18], a finding that would be surprising if only the previously made statements in this review were taken into account.…”
Section: Acute Hypoxia: Stimulusmentioning
confidence: 71%
See 1 more Smart Citation
“…After 72 hours exposure to 1% oxygen, the proliferative rate of fibroblasts increases by 71% [10]. Low oxygen tensions have been shown to initiate clonal expansion of fibroblasts [18], a finding that would be surprising if only the previously made statements in this review were taken into account.…”
Section: Acute Hypoxia: Stimulusmentioning
confidence: 71%
“…In vitro it has been shown that human dermal fibroblasts decrease their proliferative activity under chronic hypoxia (six passages at 1% O 2 ) [10]. In vivo oxygen tissue tensions of nearly 5-15 mmHg were measured at the threshold between the epicenter of the wound and granulation tissue where leukocytes (mainly macrophages) were most commonly seen.…”
Section: Role Of Oxygen On Cellular Levelmentioning
confidence: 99%
“…Prolonged hypoxia is one of the most common causes of chronic wounds [32], where healing fails to produce anatomical and functional integrity [33]. Siddiqui et al [86] noted that fibroblast cells placed in chronically low oxygen levels over 72 h exhibited a 50 per cent decrease in population doublings, a 1.48-fold reduction in collagen production and a 3.1-fold decrease in TGF-b production relative to a standard oxygen system. These observations confirm the findings that chronic hypoxia reduces collagen production and that fibroblast proliferation is greatly inhibited in this case [87].…”
Section: Results (A) Normal Wound Healingmentioning
confidence: 99%
“…However, exposure to prolonged culture in hypoxic conditions ( > 1 week), thus, mimicking an ischemic dermal environment, did not support these processes. 112 Similarly, other studies using dermal fibroblasts have reported up-regulated expression of pro-a1 (I) 113 and (III) collagens 114,115 after acute exposure to hypoxic conditions in vitro, followed by decreased expression in response to prolonged hypoxia. 114,115 Under hypoxic conditions dermal fibroblastproduced collagen cannot be synthesized or crosslinked effectively, since the enzymes required for collagen polymerization and crosslinking, prolyl hydroxylase, lysyl hydroxylase, and lysyl oxidase, all require molecular oxygen as a cofactor to perform their biological function in the collagen synthesis and maturation pathway.…”
mentioning
confidence: 82%